Structural Aspect of Hydroxyethyl-Starch-Anticancer-Drug-Conjugates as State-of-the-Art Drug Carriers - Koushik Chandra; Sansa Dutta; Haradhan Kolya; Chun-Won Kang (MDPI AG, 2023)
Cancer is a genetic disorder and its treatment usually requires a long time and expensive diagnosis. While chemotherapy is the most conventional approach in treating most cancers, patients often suffer from undesired side effects due to various pharmacokinetic aspects. To address this issue, target-oriented drug-delivery systems (DDS) or pulsatile drug-delivery systems (PDDS) have recently been developed as an alternative tool that takes care of the entire pharmacodynamic activities of drug action. Hydroxyethyl starch (HES) has emerged as an effective clinical tool for delivering anticancer agents into target cells. These systems have demonstrated significant potential as anticancer drug carrier conjugates through their innate pharmacokinetic properties with their safety profile. This review focuses primarily on the structural aspect during the use of HES or HES-based polymers as carriers for delivering well-known anticancer drugs. This review also indicates a perspective on the long-term research needed for the sake of improving modern drug-delivery systems based on HES polymers and in the form of nanocarriers.